Child Care and Protection in Perspective of Legislation, Human Rights and Islamic Law - Lisma Lisma; Roykhatun Nikmah (Al-Bayyinah, 2021)
The empirical reality regarding the issue of care and protection for children is still a global concern. It is necessary to find rules regarding the protection and care of children. Comparing several rules in legislation, human rights and Islamic law in strengthening the position of children as human beings who must receive care and protection. This research is a literature review with a normative juridical approach. Examining various literatures by focusing on aspects of laws and regulations related to care, child protection, human rights and Islamic law. The techniques of analysis used were descriptive and comparative. The findings of this study indicate that child care and protection falls into the category of fulfilling human rights. Child protection is in line with the universal principles of human rights and has a legal umbrella and the power to obtain care and protection. However, the existing regulations have not been maximally implemented. In Islamic law, children have a very high guarantee of protection, this is included in the category of caring for children as the goal of sharia (maqashid syari'ah). The implication of this finding is that the protection of children's rights cannot be negotiated, because the state and religion have provided protection, so what must be enforced is the supervision of the fulfillment of children's rights.